Pressure transients in water engineering : a guide to analysis and interpretation of behaviour - Ellis, John, 1946 January 5- (Thomas Telford, 2008)
This volume presents explanations of equations relating to pressure transients in water engineering and introduces relevant computer analysis techniques. It includes case studies and assessments of systems and equipment.
Keywords: Unsteady flow (Fluid dynamics); Pipelines -- Fluid dynamics.; elektronické knihy; electronic books